2021
DOI: 10.3390/ijms222413609
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Dysbiosis and Relation to the Efficacy of Proton Pump Inhibitors in Functional Dyspepsia

Abstract: Proton pump inhibitors (PPI) may improve symptoms in functional dyspepsia (FD) through duodenal eosinophil-reducing effects. However, the contribution of the microbiome to FD symptoms and its interaction with PPI remains elusive. Aseptic duodenal brushings and biopsies were performed before and after PPI intake (4 weeks Pantoprazole 40 mg daily, FD-starters and controls) or withdrawal (2 months, FD-stoppers) for 16S-rRNA sequencing. Between- and within-group changes in genera or diversity and associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…In addition, PPIs have been used as short-term drugs to improve the gastrointestinal symptoms of SLE. However, some studies have found that the long-term use of PPIs could have adverse effects [ 24 , 25 ]. Future research might hence benefit from longer trials where PPI treated SLE patients are followed for longer periods of time collecting samples at various points in time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PPIs have been used as short-term drugs to improve the gastrointestinal symptoms of SLE. However, some studies have found that the long-term use of PPIs could have adverse effects [ 24 , 25 ]. Future research might hence benefit from longer trials where PPI treated SLE patients are followed for longer periods of time collecting samples at various points in time.…”
Section: Discussionmentioning
confidence: 99%
“…Increased presence of luminal Streptococcus was reported in FD compared to controls and correlated to upper GI symptoms in both PDS and EPS subgroups ( Fukui et al, 2020 ). We recently provided evidence for the involvement of luminal Porphyromonas in FD, with an inverse association of the genus abundance to GI symptoms and duodenal eosinophilia, suggesting a link with immune activation ( Wauters et al, 2021g ). In addition, the efficacy of a combination of two spore-forming probiotic Bacillus strains was demonstrated in a placebo-controlled study in FD, with decreased peripheral Th17 signaling and increased Faecalibacterium and Roseburia in stools, suggesting immunomodulatory properties of probiotic therapy in FD ( Wauters et al, 2021f ).…”
Section: Factors Related To Immune Activationmentioning
confidence: 99%
“…Dyspeptic patients also demonstrated increased anaerobic metabolism in the gastric microbial community in conjunction with increased Pseudoclavibacter and Tannerella , increased Veillonella, Cohnella, Sporolactobacillus, Propionigenium in saliva, and a higher duodenal prevalence of Rothia , Clostridium, Haemophilus , and Actinobacillus species 90 . A recent study demonstrated decreased duodenal mucosal Neisseria and Porphyromonas abundance in FD patients and controls prior to treatment with PPIs, but no differences in microbial load 91 . These findings are presented in Table 1.…”
Section: Introductionmentioning
confidence: 72%